2022
DOI: 10.1111/opn.12460
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the use of participatory action research to implement evidence‐based guidance on dementia palliative care in long‐term care settings: A creative hermeneutic analysis

Abstract: Background Dementia affects a large proportion of society and places a significant burden on older people and healthcare systems internationally. Managing symptoms at the end of life for people with dementia is complex. Participatory action research can offer an approach that helps to encourage implementation of evidence‐based practices in long‐term care settings. Methods Three evidence‐based guidance documents (pain assessment and management, medication management, nutrition and hydration management) were int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…In KM studies for HCPs, program adherence was only reported when deviations from intended delivery occurred. Deviations occurred to better accommodate staff schedules, promote uptake and as a result of time constraints 17,53,75 . Technology barriers greatly impacted adherence in one study, forcing a transition from web-delivered modules to paper copies 41 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In KM studies for HCPs, program adherence was only reported when deviations from intended delivery occurred. Deviations occurred to better accommodate staff schedules, promote uptake and as a result of time constraints 17,53,75 . Technology barriers greatly impacted adherence in one study, forcing a transition from web-delivered modules to paper copies 41 …”
Section: Resultsmentioning
confidence: 99%
“…Penetration is the reach or integration of an intervention into a service setting 25 . Penetration was examined in 2 KT-I programs; 75,97 target outcomes partially improved in both studies. After a guideline initiative, 76.4% of nurses trained reported familiarity with program information for nursing home resident pain, indicating education reached and was attended to by a majority of nurses 79 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 2530 retrieved studies, 193 were ultimately included 6,7,11–201 . The PRISMA-ScR diagram (Figure 1) shows the study selection process and reasons for full-text exclusion.…”
Section: Resultsmentioning
confidence: 99%
“…It involves stakeholders as active participants in the research process, not merely as 'subjects' but as co-researchers. It is an approach that is responsive and committed in providing solutions to real world problems [37] and has been particularly valuable in health and social care research in providing crucial insights into the barriers and facilitators of implementing evidence-based practices and expanding understanding of complex situations [38][39][40]. Workplace learning is a core feature of many action-oriented approaches such as participatory research and includes an emphasis on experiential learning [41,42] and facilitation of critical reflection in the creation of new professional knowledge [43,44].…”
Section: Design and Proceduresmentioning
confidence: 99%